2022
DOI: 10.1002/asna.20220003
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological constraints on bulk viscous f(Q,T) gravity

Abstract: In the General Theory of Relativity (GR) gravitational interactions are described by the scalar Ricci curvature. But there exists another class of modified gravity theories equivalent to GR, described by the torsion tensor or non‐metricity scalar. One of such theories, investigated in this paper is ffalse(Q,Tfalse) gravity, built from the arbitrary function of non‐metricity scalar non‐minimally coupled to the trace of stress‐energy tensor. Current work is aimed on the linear ffalse(Q,Tfalse)=αQ+βT gravity, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 118 publications
1
9
0
Order By: Relevance
“…The model does not exhibit a late time acceleration for zero or [72]). OHD corresponds to the Observational Hubble Data set with 57 entries [73] large positive values of 𝜆. However, similar to Moradpour et al's results, we get a late time acceleration for negative values of 𝜆, which could explain the observation.…”
Section: Standard Rényi Hde and Its Inconsistenciessupporting
confidence: 88%
See 2 more Smart Citations
“…The model does not exhibit a late time acceleration for zero or [72]). OHD corresponds to the Observational Hubble Data set with 57 entries [73] large positive values of 𝜆. However, similar to Moradpour et al's results, we get a late time acceleration for negative values of 𝜆, which could explain the observation.…”
Section: Standard Rényi Hde and Its Inconsistenciessupporting
confidence: 88%
“…Hubble parameter (𝐻 (𝑧)) as a function of redshift (𝑧) for different values of 𝜆 with standard Rényi HDE density (with Ω 𝑚0 = 0.315 and 𝐻 0 = 67.4 km/s/Mpc[72]). OHD corresponds to the Observational Hubble Data set with 57 entries[73]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the resulting theory differs from well-known f (R, T) gravity [25] and f (T, T ) gravity [26] in that it is a novel modified gravitational theory based on a more general geometric framework than Riemannian geometry (Weyl geometry), with no curvature-equivalent and no torsion-equivalent, and its cosmological implications are very interesting. In the literature, there are active works in the framework f (Q, T) gravity theory [27][28][29][30][31]. Thus, there is a motivation to examine several theoretical, observational and cosmological aspects of f (Q, T) gravity.…”
Section: Introductionmentioning
confidence: 99%
“…f (Q, T ) gravity has been deeply studied recently. The Chaplygin gas in the context of f (Q, T ) was explored in [18], observational constraints of f (Q, T ) gravity functions are presented in [19][20][21][22][23][24][25][26][27][28][29] and the linear theory of cosmological perturbations were explored in [30]. In addition to this, it has been shown that a particular quadratic function on…”
Section: Introductionmentioning
confidence: 99%